Coaching and Implementation: Insights from a Field Experiment in Danish Schools - Simon Calmar Andersen; Bastien Michel; Helena Skyt Nielsen (Institute of Labor Economics (IZA), 2025)
We study the effect of peer coaching separately from the effect of training on teachers' implementation of new teaching techniques. We conducted a preregistered field experiment involving 68 teachers and 1,490 students in Denmark. Teachers in an active control group took part in a teaching program that introduced new teaching techniques. On top of the teaching program, the treatment group received coaching from peers. External observers, blinded to the treatment status, assessed teachers' use of the program techniques in the classroom. While we observe increased transfer to teachers' practices, the overall effects are mixed, calling for caution.
Keywords: I21; J24; 330; coaching; knowledge transfer; school teachers; field experiment